Hibiscus sabdariffa (ROSELLE) POLYPHENOL-RICH EXTRACT PREVENTS THE AORTIC OXIDATIVE DAMAGE IN TYPE 1 DIABETIC RATS (Jurnal Teknologi (Sciences & Engineering), 2018)
Diabetes mellitus complications mainly occur due to the oxidative stress-related condition. Thus, this study aimed to investigate the protective effect of the polyphenol-rich extract of Hibiscus sabdariffa (roselle) (HPE) on the aorta of streptozotocin-induced diabetic rats. Twenty-four male Sprague-Dawley rats were divided into four groups (n=6/group); non-diabetes control (NDM), diabetes (DM), diabetes treated with HPE (DM+HPE) and metformin (DM+MET). HPE and metformin were given orally at the dose of 100mg/kg and 150mg/kg respectively for eight weeks duration. At the end of the experiment period, blood pressure was measured before the rats were sacrificed. Blood was taken for measurement of plasma glucose and lipid levels whilst aorta was excised for oxidative stress and histological evaluation. Results showed that HPE treatment reduced plasma glucose level, blood pressure and improved dyslipidemia significantly (p<0.05) in DM+HPE group compared to DM group.Â  Malondialdehyde (MDA) and advanced oxidation protein product (AOPP) levels were significantly decreased (p<0.05) while GSH level was significantly increased (p<0.05) in DM+HPE group compared to DM group. No histological changes observed in the aorta of all diabetic groups compared to NDM group. In conclusion, HPE might have a potential in minimizing the risk of vascular damage in diabetic conditions.Â